Pharmacokinetics and bioequivalence of low-dose clopidogrel in healthy Chinese volunteers under fasted and fed conditions. Issue 5 (October 2019) - Gong, Liying; Fu, Chengxiao; Bi, Lucun; Kuang, Yun; Guo, Chengxian; Wei, Guolan; Yan, Zhaofeng; Huang, Jie; Yang, Guoping
Abstract: Clopidogrel is an antiplatelet drug whose performance at a low dose (25 mg) have not been evaluated in Chinese patients, who may be subject to different effects from Caucasians. We carried out this evaluation and compared a generic (Taijia) and a reference drug (Plavix ® ). We evaluated Taijia and Plavix ® in 128 subjects, with 64 in a fasted state and 64 receiving a high-fat diet, and computed Cmax, AUC0-∞, and AUC0-t . Reference-scaled average bioequivalence (RSABE) methods and average bioequivalence (ABE) methods were used, and adverse events were assessed. Average maximum plasma concentrations (Cmax ) of clopidogrel were significantly greater after 25 mg dose under fed conditions compared to fasted. Reference-scaled Cmax, AUC0-t, and AUC0-∞ were higher than the 0.294 cutoff during fasted, meeting RSABE criteria. Under fed conditions, SWR for AUC0-t and AUC0-∞ were lower than 0.294, permitting use of ABE. The 90% confidence intervals for AUC0-t and AUC0-∞ indicated bioequivalence. Pharmacokinetic parameters differed between fasted and fed states. The generic product was bioequivalent to the reference drug, and was safe and well tolerated. This suggests that they can be used interchangeably in a clinical setting. Graphical abstract: Image 1